Adhesive Joints Testing of Ceramic and Anti-Ballistic Fabrics - Jan GODZIMIRSKI; Roman GIELETA; Marek ROŚKOWICZ (Problemy Mechatroniki)
The research results of adhesive joints used in the manufacture of bulletproof vests were presented. The joints were prepared on the basis of polyethylene and aramid fabrics and ceramic tiles of SiC and Al2O3 types. For joining the materials, the following adhesives dedicated to bonding polymeric materials were used: BONDICX 01 CX-80, Poxipol 10 min, LOCTITE 3038, Scotch-Weld 8010, Professional Silicone Black, and Terostat M9399. It was found that the polyethylene fabrics HB50 and HB26 401184C ROLL ROLL 401400B, due to their low interlaminar strength and lack of compliance to supersaturation, are not suitable for their adhesive bonding with the tiles. On the basis of research, the test specimens were proposed which in the best way represent the loading of ceramic tiles which are bonded to the fabric. Tests with using such specimens demonstrated that the adhesive BONDICX 01 is the best solution for such applications.